“Desarrollo de un sistema SCADA para el control de dos ejes con servomotor y motor a pasos”. - Salguero Zapata, Jose David (2024)
The following document focuses on the development of a SCADA system intended for the control of the servomotor in the X-axis and the stepper motor in the Y-axis; using communication protocols between the equipment involved, considering the technical specifications of each of the devices that interact for the constitution of a SCADA system, which solves the difficulty of synchronism that both motors lack. To establish the interaction between the PLC and the computer, this project used RS232 communication. It was discovered that the RS485 protocol was used for communication between the PLC and the HMI. Software tools that assisted in the creation of a remote server and a program to retrieve data hosted on the server included KEPServer, designed for server creation, and Node-Net, designated for local and remote control, monitoring, and supervision of data. Finally, it determined that the use of the SCADA system has a direct impact on the manipulation of the equipment involved in the acquisition, control, and supervision of data; reaching an improvement of 1.51% about the nominal factory errors of the motors.